Factores familiares que influyen en el rendimiento académico de los estudiantes de un Centro Educativo del corregimiento de Porciosa, Albania – La Guajira (2023)
The objective of this research was to identify the family factors that influence the academic performance of the students of the Eduardo Pinto Educational Center in the town of Porciosa, municipality of Albania – La Guajira. Regarding the methodology, it was descriptive, with a qualitative approach and field design; The sample was made up of 8 students from the fifth grade of the Eduardo Pinto Educational Center who range in age between 10 and 12 years of age. To collect information, an in-depth interview was applied with open questions properly structured under the categories: Family factors and academic performance and the subcategories: Family conflicts, family disintegration, economic difficulties, parental education, low school performance, cultural level, physiological, psychological and pedagogical factors and positive and negative compensations.